2016
DOI: 10.1177/0042085916674060
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Meanings of (In)Equity: Remaking School District Tracking Policy in an Era of Budget Cuts and Accountability

Abstract: How do school district administrators make sense of educational equity as they undertake reform? This study examines tracking policymaking in two urban school districts. Using case studies and an interpretive approach, the study highlights school district leaders’ shifting ways of making sense of tracking and (in)equity while facing achievement gaps, accountability pressures, budgets cuts, and support for tracking. Even after the emergence of powerful opposition, we find that district administrators continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 61 publications
0
44
1
Order By: Relevance
“…Finally, a growing body of research investigates the intersection between district leaders' reasoning and race, class, and language (Turner, 2015(Turner, , 2020Turner & Spain, 2016). In a study of districts' responses to changing demographics, Turner found that district leaders' reasoning about problems and solutions was laden with explicit and implicit racial discourse.…”
Section: The Nature Of Deliberation In District Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a growing body of research investigates the intersection between district leaders' reasoning and race, class, and language (Turner, 2015(Turner, , 2020Turner & Spain, 2016). In a study of districts' responses to changing demographics, Turner found that district leaders' reasoning about problems and solutions was laden with explicit and implicit racial discourse.…”
Section: The Nature Of Deliberation In District Decision Makingmentioning
confidence: 99%
“…Reasons may be layered with discourse related to race, class, and language (Turner, 2015(Turner, , 2020Turner & Spain, 2016). Deliberators may evoke individual or cultural deficit discourses.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty is another variable under scrutiny when discussing student achievement gaps in state-mandated tests (Alexander & Jang, 2020;Baker, 2016;Clotfelter et al, 2009;Fernald et al, 2013;Harwell, 2018;Murnane et al, 2006;Olszewski-Kubilius et al, 2018;Phillips et al, 1998;Turner & Spain, 2020). This, according to researchers, is because Black and Hispanic students are more likely to experience the negative effects of poverty (e.g., low household income and unemployed family members) than White students (Reeves et al, 2016).…”
Section: Journal Of Educational Research and Practice 202mentioning
confidence: 99%
“…Results of the Games-Howell post hoc test revealed there were significant mean differences (p = .000) between all the combinations of the four instructional time configurations with the exception of the difference between the 61-79 minute block all year and the A/B 80-90 minute block all year instructional time configurations (p = .083). Then, because poverty has been identified as a variable with potential to significantly impact student achievement (Alexander & Jang, 2020;Anderson, 1993;Baker, 2016;Clotfelter et al, 2009;Fernald et al, 2013;Guo & Harris, 2000;Harwell, 2018;Kuhfeld et al, 2018;Murnane et al, 2006;Olszewski-Kubilius et al, 2018;Phillips et al, 1998;Turner & Spain, 2020), an ANCOVA was conducted on the interaction between instructional time configuration and social studies accountability test results using a covariate, Poverty Index, to control for student poverty level. Table 2 shows the result of this analysis.…”
Section: Research Questionmentioning
confidence: 99%